JUAL BELI HEWAN TONAK LOPEH KAJIAN HUKUM ISLAM: Studi di Desa Gema Kampar-Kiri Hulu - Nasyiah, Iffaty (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The background of this study is the habit of Gema Kampar Kiri villagers at Hulu district in terms of buying and selling cattle. They call it,â€œtonak lopehâ€ transaction. Its practice is different from the common transaction practice i.e the purchased livestock does not directly switch to the buyer and it is purchased only partially, ranging from one sixteenth to a half. Another uniqueness is that these cattle are not kept in the cage, but are released in the meadow. Based on this background, the researchers formulate a problem that is how the view of Islamic law about the practice of this transaction. This research is an empirical law research with sociological juridical approach. The result of this research is the sale of â€œpartialâ€ livestock in the opinion of Imam Nawawi in his book Minhaj al Thalibin is in accordance with Islamic law because the object of sale and purchase should not be in part, unless the value and benefit from the goods is not reduced.